Dancing Postcolonialism The National Dance Theatre Company of Jamaica - Sörgel, Sabine (TanzScripte, 2007)
This book presents the first in-depth critical and historical examination of the internationally renowned National Dance Theatre Company of Jamaica (NDTC) in the context of postcolonial theatre. Combining a postcolonial theoretical framework with performance studies and dance analysis, the study examines the interrelationship of Jamaican modern dance theatre aesthetics and the Caribbean's complex cultural genealogy since 1492. Addressing issues of postcolonial nationalism and Jamaican identity politics, the book provides the first comprehensive study of the NDTC's modern dance theatre works as it situates dance theatre choreography at the centre of postcolonial independence politics and cultural theory in the Caribbean.